From birth to death: The hardworking life of Paneth cell in the small intestine - Cui, Chenbin; Wang, Fangke; Zheng, Yao; Wei, Hongkui; Peng, Jian (Frontiers in Immunology, 2023)
Intestinal Paneth cells play an important role in host-microbiota interactions. At the origin of Paneth cell life, several pathways, such as Wnt, Notch and BMP signaling, act on the differentiation of Paneth cells. As a particular group of epithelial cells migrating downward after lineage commitment, Paneth cells reside in the base of crypts and possess abundant granules in their apical cytoplasm, and the products in the granules partly include antimicrobial peptides and growth factors. Antimicrobial peptides shape the composition of microbiota and defend from mucosal penetration by commensal and pathogenic bacteria to protect intestinal epithelial barriers. Growth factors derived from Paneth cells benefit the normal functions of intestinal stem cells. The presence of Paneth cells ensures the sterile environment and clearance of apoptotic cells in crypts to maintain intestinal homeostasis. Various types of programmed cell death, such as apoptosis and necroptosis, occur in Paneth cells at the end of their lives. During intestinal injury, stem cell features are acquired by Paneth cells to restore intestinal epithelial integrity. In view of the crucial involvements of Paneth cells in intestinal homeostasis, research on Paneth cells has been rapidly developed these years, and recent reviews on Paneth cells mainly focused on their functions of antimicrobial peptide secretion and intestinal stem cell support. This review aims to summarize the approaches to study Paneth cells and introduce the whole experience of Paneth cells from birth to death.